Agronomic performance and remote sensing assessment of organic and mineral fertilization in rice fields - Marti-Jerez, Karen; Català-Forner, Mar; Tomàs, Núria; Murillo, Gemma; Ortiz, Carlos; Sánchez-Torres, María José; Vitali, Andrea; Lopes, Marta S. (Frontiers in Plant Science, 2023)
Rice is a major cereal crop, and its cultivation consumes large amounts of chemical nitrogen fertiliser. The negative environmental effects, rising prices, resource limitations, and geopolitical conflicts related to mineral fertilisers (MIN) have sparked the need to seek alternative nutritionally sustainable sources such as animal manure and remote sensing methods to improve resource use efficiency. This study assessed the long-term impact of organic fertilization in rice, covering yield, utilization safety, nutritional patterns, and nutritional monitoring with remote sensing through real-time Sentinel-2 implementation. A six-year experiment was conducted to assess the long-term effects of integrated fertilisation with pig slurry (PS) or chicken manure (CM) with MIN compared to stand-alone MIN and zero-fertilised strategies on agronomic traits, yield, and crop spectral response in dry-seeded flooded rice fields. Generally, the cost effective combined organic strategies resulted in a yield loss of 13% for PS and 15% for CM, producing twice as much as the zero-fertilised strategy and the PS exhibited the lowest nitrogen loss through leaching. All fertilisation strategies resulted in rice grains with heavy metal contents within safety levels for human consumption. N deficiency was perceived at the final vegetative stages of organic-fertilised plants affecting yield and yield related traits, therefore suggesting a non-optimal fertiliser management. This early nutritional deficiency is detected by NDVI Sentinel-2 readings. Sentinel-2 may provide accurate spatial information about the crop development and fertiliser requirements. The research leaned towards the adoption of cost-effective organic fertilizers, highlighting reduced nitrogen loss through leaching in the PS strategy. However, organic fertilizer applications presented trade-offs, decreasing rice yields compared to mineral fertilization.